PELAYANAN PUBLIK SEBAGAI INSTRUMEN MEWUJUDKAN PEMERINTAHAN DESA YANG BAIK MELALUI PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA DESA PASIR PETEUY - Firdausa, Muhammad Bintang; Sugiarto, Refania Varetta; Saputri, Wulan Sari; Harmonis, Riska (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Virtue in Higher Learning. Where the function of both instructors and students is integral to the nature of the activity. The goal of PKM (Community Service) projects is to bring together faculty, students, and members of the community in an effort to raise consciousness about local issues. The government, as well as regional, sub-district, and village administrations, are required to actively participate in the Population Administration Services system, which is designed to ensure that all individuals are protected while applying for and receiving population documentation, free from discrimination. Observation, interviews, and documentation are the main tools for gathering information in this qualitative descriptive research method. Population administration services grounded on good governance principles are essential to enhancing the quality of public services. This is driven by the need for public service providers in population administration services that exhibit excellent governance, as well as the societal aspirations for quality public services during this decentralization age.